OPTIONS FOR REGISTRATION OF THE LUNGS MAXIMUM MECHANICAL ACTIVITY, WHICH IS AIMED AT OVERCOMING INTERNAL-LUNG RESISTANCE - K. F. Tetenev; T. N. Bodrova; T. S. Ageeva; A. I. Karzilov; F. F. Tetenev (Бюллетень сибирской медицины)
The paper presents the results of assessing general and elastic lung hysteresis in 21 healthy volunteers and 28 patients with community-acquired pneumonia. Negative elastic hysteresis was detected in 14 healthy volunteers and 18 patients with community-acquired pneumonia. For the first time ever, it was demonstrated that, under the conditions of an interrupted air flow, 4 healthy volunteers and 2 patients with community-acquired pneumonia were characterized with the inversion of not only elastic but also general lung hysteresis. In case of pneumonia, despite the increase in tissue friction resulting from the generalized escalation of the alveolar-capillary permeability, the inversion of both elastic and general lung hysteresis takes place as often as in healthy people. It can be explained with the intensification of the mechanical activity of the lungs as a compensatory reaction in the mechanical system of the external respiration organs in case of pneumonia.